Constituição e operacionalização da folga orçamentária em empresas familiares - Silva, Vanessa Ramos da (2023)
In order to obtain institutional legitimacy, preserve its internal functioning and expand its conditions of continuity, companies must optimally control their organizational resources. The concept of budget slack represents the upper margin of resources available to decision makers, in order to contribute to the maximum performance of the organization's productive capacity or provision of services. The use and operationalization of budgetary slack happens according to the company's management structure, being an element that influences the business budget according to the Management Control System (SCG) practiced by managers. Therefore, as companies with different structures and management compositions, they make use of budgetary slack in their budgeting system. The dynamics of social phenomena that involve the relationship between individuals and the organization in which they participate can be understood under the central prism of Giddens' Theory of Structuring (2009), the duality of structure (managers and company structure connected by three modalities: interpretative scheme, ease and norm). Strategies for using budgetary slack in family businesses can be divergent, as management compositions can be heterogeneous. In this way, the objective is to investigate the constitution and operationalization of budgetary slack in the processes of control, planning and managerial decision involving family businesses from the perspective of Structuring Theory. Two case studies were carried out in family businesses with different forms of management composition, being a company in the industry and commerce sector that has predominantly family management and another company in the wholesale sector with management composed of non-family members. The research approach was qualitative and for the construction of the data interviews were conducted with 11 participants in the budget process with the data analyzed using the "template analysis" approach (KING, 2004). The analysis codes explored in the scripts were grouped into four categories: manager profile, family involvement and Constitution and operationalization of budgetary slack. Among the main results that were observed in the light of the Theory of Structuring, referring to the interaction between managers (agents) and the structures/rules of family businesses, it is noteworthy that both companies have the budget as a strategic management tool. Managers participate in the elaboration and execution process, the Controllers of both companies are present in all stages of the budget process, clarifying the duality through interpretation and communication of the rules of the structure. It was noticed in the company where the presence of the family is predominant that the strategic decisions related to the budget and budgetary slack may not be fully shared with all management members. In the company with non-family members, the strategic budget information is restricted to certain hierarchical levels, CEO and Directors. Finally, it is possible to see the operationalization of budgetary slack in the two companies analyzed, but knowledge and determination of concession restricted to family members or senior positions.